PENGUJIAN EMPIRIK ATAS EKSPOSUR EKONOMI YANG DIHADAPI OLEH PERUSAHAAN SEKTOR OTOMOTIF DI INDONESIA - Ghurub, Romikul (Department of Management, 2014)
The purpose of the research is to know whether the automotive sector companies operating in Indonesia is facing economic exposure. This study uses the Distributed Lag regression to determine whether there is economic exposure that must be faced by the automotive subsector in Indonesian companies listed on the Indonesia Stock Exchange during the period 2008 to 2013 or not.The results of the analysis show that the effect of the company's external economic exposure in the show by the exchange rate against foreign currencies (U.S. dollar and Japanese yen) are not shown to significantly affect the price of shares in companies listed automotive sector The Indonesia Stock Exchange. The results of this analysis can occur due to factors that affect economic exposure not only fixated on the exchange rate against foreign currencies but also there are other factors that affect the economy, such as interest rates and inflation.The results of simultaneous test (F test ) and partial test ( t test ) which found results that support each addition has no significant effect , the rupiah exchange rate against the U.S. Dollar and Japanese Yen also has a coefficient of determination with such a small proportion is 2.8 % and 0.01%. Small proportion of this which reinforce that the rupiah exchange rate against foreign currencies does not have an influence on company's stock price. Keywords: Economic Exposure, Exchange Rate, Stock Price, Regression Distributed Lag